Case Report: Adaptive radiotherapy in the radiation salvage of prostate cancer - Montalvo, Steven K.; Meng, Boyu; Lin, Mu-Han; Park, Chunjoo; Desai, Neil B.; Hannan, Raquibul; Garant, Aurelie (Frontiers in Oncology, 2022)
Adaptive radiotherapy has the potential to reduce margins, improve target coverage, and decrease toxicity to organs at risk (OARs) by optimizing radiation delivery to daily anatomic changes. Salvage for locally recurrent prostate cancer after definitive radiation remains a challenging clinical scenario given the risks to normal tissue in a setting of re-irradiation. Here, we present a case series of five patients with locally recurrent prostate cancer treated with an adaptive online linear accelerator or a 3-T MR-based linear accelerator to demonstrate excellent target coverage. All patients completed the planned treatment course with acceptable acute toxicities but a short follow-up time does not inform subacute/late toxicities.